1979
DOI: 10.1159/000179043
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Glucagon and Insulin in Hypophysectomized Rats: Effect of Tolbutamide

Abstract: Normal and hypophysectomized (hypox) rats, fed ad libitum, received intraperitoneal injections of tolbutamide (75 mg/kg/day) or of saline for 6 weeks. 24 h after the last injection, blood samples were taken for glucose, insulin and glucagon determinations. In normal rats, tolbutamide treatment did not alter serum glucose, insulin and glucagon, although it suppressed the secretion of insulin and glucagon by the pancreatic islets. In hypox rats, tolbutamide decreased serum glucose and insulin, elevated serum glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Glucose stimulated the secretion of insulin, but no quantitative conclusions could be drawn from this single experiment. Using the same preparation, insulin secretion was found decreased 3 weeks after hypophysectomy, while in a dynamic study the first phase of insulin release was found to be depressed 1 week and the second phase 5 weeks after removal of the pituitary gland [3], When pieces of rat pancreas or isolated islets were stimulated with glucose or tolbutamide, an impaired insulin biosynthesis and release was observed 3-13 weeks after hypophysectomy [2,4,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose stimulated the secretion of insulin, but no quantitative conclusions could be drawn from this single experiment. Using the same preparation, insulin secretion was found decreased 3 weeks after hypophysectomy, while in a dynamic study the first phase of insulin release was found to be depressed 1 week and the second phase 5 weeks after removal of the pituitary gland [3], When pieces of rat pancreas or isolated islets were stimulated with glucose or tolbutamide, an impaired insulin biosynthesis and release was observed 3-13 weeks after hypophysectomy [2,4,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%